Hubungan Minat Belajar Matematika dengan Hasil Belajar Matematika di Sekolah Dasar - Zen, Halimah; Abidin, Zainal; Masniladevi, Masniladevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThis study aims to determine whether there is a relationship between the interest in learning mathematics and the mathematics learning outcomes of class V students of the Public Elementary School in Cluster I of Ampek Angkek District. This type of research is correlational research. The sample in the study amounted to 56 grade V students of the Public Elementary School in Cluster I Ampek Angkek Subdistrict selected based on systematic sampling techniques. The results of the calculation of research data using the Pearson Product Moment formula obtained r count = 0.716> r table = 0.2632 and a significance value of  0,000 <0,05 which means Ho is rejected and Ha is accepted, so the hypothesis says "there is a positive relationship between interest in learning mathematics with the results of mathematics learning in the fifth grade students of the Public Elementary School in Cluster I Ampek Angkek District. Keywords: Interest in Learning, Learning Outcomes, Mathematics